2015
DOI: 10.1007/s10753-015-0213-2
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role for Acrolein in Neutrophil-Mediated Chronic Inflammation

Abstract: Neutrophils (PMNs) are key mediators of inflammatory processes throughout the body. In this study, we investigated the role of acrolein, a highly reactive aldehyde that is ubiquitously present in the environment and produced endogenously at sites of inflammation, in mediating PMN-mediated degradation of collagen facilitating proline-glycine-proline (PGP) production. We treated peripheral blood neutrophils with acrolein and analyzed cell supernatants and lysates for matrix metalloproteinase-9 (MMP-9) and prolyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…These findings are consistent with a previous cohort study reporting higher urinary 3HPMA concentrations in smokers compared with nonsmokers, and associations between increased 3HPMA and CVD risk measures including platelet-leukocyte aggregates and Framingham Risk score [20]. Previous studies have shown acrolein exposures can induce cardiovascular injury in animal models [17,19], induce or exacerbate dyslipidemia, and modify lipoproteins [43,44], and may contribute to neutrophil-mediated inflammation [45]. HIV infection is associated with increased inflammation [46,47] and renal dysfunction [48], which may further increase acrolein levels and its impact on cardiovascular disease [16,39,42,49].…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with a previous cohort study reporting higher urinary 3HPMA concentrations in smokers compared with nonsmokers, and associations between increased 3HPMA and CVD risk measures including platelet-leukocyte aggregates and Framingham Risk score [20]. Previous studies have shown acrolein exposures can induce cardiovascular injury in animal models [17,19], induce or exacerbate dyslipidemia, and modify lipoproteins [43,44], and may contribute to neutrophil-mediated inflammation [45]. HIV infection is associated with increased inflammation [46,47] and renal dysfunction [48], which may further increase acrolein levels and its impact on cardiovascular disease [16,39,42,49].…”
Section: Discussionsupporting
confidence: 91%
“…Due to its potent capacity for degrading PGP, reduced abundance of this protein could help to sustain local inflammation in the testes. Interestingly, both the production and activity of LTA4H is reduced by acrolein [39], a byproduct of lipid peroxidation, which could be produced by developing spermatozoa undergoing oxidative stress [40]. While inflammation associated with obesity is primarily propelled by adipose tissue, reduced levels of SUGT1 and LTA4H could help to maintain inflammation in the testes of obese men.…”
Section: Discussionmentioning
confidence: 99%
“…PVL additionally increased the formation of acrolein-bound proteins in neutrophil-conditioned plasma. Acrolein is generated by human neutrophils via the myeloperoxidase/hydrogen peroxide/chloride system 21 and by other mechanisms, and has been associated with exacerbated inflammatory and immune responses 39 , 40 as well as with ischemic stroke 41 .…”
Section: Discussionmentioning
confidence: 99%